A holistic antidoping approach for a fairer future for sport - Pitsiladis, Y.; Ferriani, I.; Geistlinger, M.; de Hon, O.; Bosch, A.; Pigozzi, F. (Current Sports Medicine Reports, 2017)
There is no doubt that sport, as a credible brand, is in crisis. The magnitude of the problem is well illustrated with a brief description of three lines of evidence in recent years that demonstrate, in the words of David Howman, former director general of theWorld Anti-Doping Agency (WADA),''We are catching the dopey dopers, but not the sophisticated ones''(6). The first line of evidence is the exposure of the cyclist Lance Armstrong as a drug cheat. The evidence now shows that the U.S. Postal Service Pro Cycling Team ran, what some consider, the most sophisticated, professionalized, and successful doping program that sport has ever seen (11). Despite being tested about 275 times in his cycling career, Lance Armstrong never failed a doping test and was only exposed by the testimonies of some of his coconspirators. A look at the prohibited methods and substances the cyclist admittedly abused include blood transfusion, erythropoietin (EPO), growth hormone, cortisol and testosterone, and testify to an antidoping problem in terms of detection of these traditional doping methods and substances. It is important to point out that the Lance Armstrong case predates many of the more positive recent antidoping developments associated with the new World Anti- Doping Code (WADC) (14), such as improved intelligence and smarter testing (e.g., Athlete Biological Passport [ABP]). The second line of suggestive evidence is the appearance of systematic and state-colluded doping in Russia; the events of which have been summarized recently (7). Briefly, an ever-increasing body of evidence is emerging which indicates that there may have been a systematic state-sponsored subversion of the drug-testing processes by the Russian government during and subsequent to the 2014 Winter Games in Sochi. Furthermore, it is alleged that from 2011 to 2015, more than 1000 Russian competitors in various sports (including summer, winter, and Paralympic sports) benefited from the state-colluded systematic doping. In the words of Richard McLaren, appointed by WADA to conduct the investigation, ''The Russian Olympic team corrupted the London Games 2012 on an unprecedented scale, the extent of which will probably never be fully established…The desire to win medals superseded their collective moral and ethical compass and Olympic values of fair play'' (12,13). While some in the media wish to take credit for exposing the Russian doping scandal (e.g., headline by the Sunday Times ''sport's dirtiest secrets'') (3), further evidence of systematic doping, and incidentally not confined only to Russia, was published by the medical commission of the international governing body for athletics, the International Association of Athletics Federations (IAAF) in 2011 (8). Specifically, information was obtained from the blood-testing program to detect altered hematological profiles in the world's top-level athletes, which the IAAF has implemented since 2001. Estimates of the prevalence of blood doping ranged from 1% to 48% for subpopulations of samples and a mean of 14% for the entire study population (8).Of particular interest, however, are the striking prevalence ranges of two countries (estimates obtained assuming doping with microdoses of EPO)-country A: 54% to 99% and country H: 21% to 87%. From the above three lines of evidence, it is clear that the antidoping process, despite an ever-increasing restriction and control, is still producing suboptimal results at best. There is, therefore, an urgent need to increase the quality and efficiency of the antidoping process to rebrand and restore the credibility of sport.